(untitled) (Communication & Society, 2011)
The news published in Deia, El Correo, El País and Gara media about gender violence in the Basque Country during the period 2002-2009 are the subject of analysis of this text. The aim of this study is, first, comparing the recommendations on the coverage of the gender-based violence have been made from different organizations and its application in journalism and, secondly, to compare different discourse strategies each of the media. This research is part of a larger study on treatment of violence in the media funded by the Spanish MICINN (reference CSO2010-19855).